2023
DOI: 10.1001/jamacardio.2022.3839
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium-Glucose Cotransporter 2 Inhibitors and Glucagonlike Peptide-1 Receptor Agonists in Patients With Diabetes and Cardiovascular Disease in Community Practice

Abstract: ImportanceRecent national guidelines recommend sodium-glucose cotransporter 2 inhibitors (SGLT2i) and glucagonlike peptide-1 receptor agonists (GLP-1 RA) in patients with type 2 diabetes (T2D) and atherosclerotic cardiovascular disease (ASCVD); yet, there are limited data on the use of these agents in contemporary community practice.ObjectiveTo evaluate the use of SGLT2i and GLP-1 RA in adults with T2D and ASCVD across a diverse sample of health care systems in the US.Design, Setting, and ParticipantsThis mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
13
1
Order By: Relevance
“…Among 321 304 patients with type 2 diabetes and ASCVD in 88 US health care systems, from January 2018 to March 2021, the use of SGLT-2 inhibitors increased from 5.8% to 12.9% and the use of GLP1-RAs from 6.9% to 13.8% (and either agent from 11.4% to 23.2%). 100 Those taking either of these agents were younger, less likely to have been hospitalized in the past year, and more likely to be taking other secondary prevention medications.…”
Section: Diabetesmentioning
confidence: 99%
“…Among 321 304 patients with type 2 diabetes and ASCVD in 88 US health care systems, from January 2018 to March 2021, the use of SGLT-2 inhibitors increased from 5.8% to 12.9% and the use of GLP1-RAs from 6.9% to 13.8% (and either agent from 11.4% to 23.2%). 100 Those taking either of these agents were younger, less likely to have been hospitalized in the past year, and more likely to be taking other secondary prevention medications.…”
Section: Diabetesmentioning
confidence: 99%
“…Our study found that, although the proportion of SGLT2i increased year by year, the overall utilization rate of SGLT2i was low in DKD patients. Previous studies have also found low rates of SGLT2i use, partly due to the high out-of-pocket costs associated with SGLT2i as a new drug 20 , 21 . In China, on the other hand, SGLT2i were about four times less expensive than before, following their inclusion in health insurance in November 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptidyl peptidase 4 inhibitors were used by 15%-18%, and, although the most use was of metformin (60%) and sulfonylureas (25%-30%), the doubling of use of SGLT2i and GLP-1RA suggests a real change in practice patterns. 5…”
Section: Cardiovascular Disease (Cvd) Outcomesmentioning
confidence: 99%
“…An electronic health record analysis of >300 000 persons with type 2 diabetes and CVD found that use of sodium‐glucose cotransporter 2 inhibitors (SGLT2i) and glucagonlike peptide‐1 receptor agonists (GLP‐1RA) increased from ~11% in 2018 to 23% in 2021. Dipeptidyl peptidase 4 inhibitors were used by 15%–18%, and, although the most use was of metformin (~60%) and sulfonylureas (25%–30%), the doubling of use of SGLT2i and GLP‐1RA suggests a real change in practice patterns 5 …”
Section: Cardiovascular Disease (Cvd) Outcomesmentioning
confidence: 99%